Analysis of Tensile and Bending Strength of Coconut Fiber Reinforcement Composite on Quasi Isotropic Laminates Stacking Sequence - Aminur Aminur; Jaka Seru Dwi Saputra; Citra Yurnidar Syah (Journal of Metallurgical Engineering and Processing Technology, 2024)
A composite is a material structure composed of two or more combinations of constituents combined macroscopically, where the two combinations do not dissolve each other. The first phase is called reinforcement, while the second phase is called matrix. This study aims to analysis the tensile and bending strength values of coconut fiber reinforced composites with a sequence of layers of quasi-isotropic fiber laminates. Experimental studies were carried out on polyester resin composites reinforced with coconut fiber in the fiber layer sequences of [0°/0°/0°], [+45°/0°/-45°] and [+60°/0°/-60°]. Tensile test specimen standards refer to ASTM D-3039 and bending test standards refer to ASTM D-7264. The results of the blistering test obtained a maximum stress of 18.3298 N/mm2 in the fiber layer sequence [0°/0°/0°] and a minimum stress of 10.8966 N/mm2 in the fiber layer sequence [+60°/0°/ -60°]. Meanwhile, the bending test results showed that the maximum bending stress was 76.065 N/mm2 in the fiber layer sequence [0°/0°/0°] and the minimum stress was 30.256 N/mm2 in the fiber layer sequence [+45°/0°/-45 °].